PREVALENCE OF PULMONARY HYPERTENSION IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE PATIENTS AND ITS CORRELATION WITH THE SEVERITY OF DISEASE (The Research of Medical Science Review, 2025)
Background: Chronic obstructive pulmonary disease (COPD) represents a major public health issue on a worldwide scale, often complicated by pulmonary hypertension (PH), which exacerbates morbidity and mortality. While the relationship between COPD severity and PH is established, data on PH prevalence in mild to moderate COPD is inconsistent. Objective: This study aimed to assess the frequency of PH in COPD patients and its correlation with disease severity in Pakistan. Design: Descriptive observational study conducted on adult COPD patients aged 30 to 80 years, presenting to the Aga Khan University Hospital (AKUH), Karachi, Pakistan from January 2017 to December 2022 Methods: All diagnosed COPD patients who had an echocardiography and a spirometry done at AKUH were included in this study. Exclusion criteria were PH due to causes other than COPD and left-sided heart disease. Pulmonary hypertension was characterized by an estimated pulmonary artery systolic pressure (PASP) of 35 mmHg or greater, as determined through echocardiographic assessment. COPD severity was classified according to GOLD guidelines. Results: A total of 236 patients were included, with a mean age of 67.06 years. PH was identified in 26.3% of patients: 21.2% mild, 3.0% moderate, and 2.1% severe. There was no significant difference in demographics, comorbidities, or COPD treatments between those with and without PH. Higher prevalence of biomass exposure was seen in patients with moderate PH (p=0.046). In multivariate analysis, increasing age (Odds Ratio [OR] 1.033, 95% Confidence Interval [CI] 1.000 – 1.067, p=0.051) was found to be independently associated with risk of developing PH. Conclusion: The estimated prevalence of PH in COPD patients is around 26.3% in our study. Advanced age, low FEV1 and biomass fuel exposure are found to be risk factors for developing PH. in COPD patients in this study. Early identification and management of PH may improve outcomes in COPD patients.